IMF Staff Papers, Volume 51, No. 1. (IMF Staff Papers; IMF Staff Papers, 2004)
This first issue of Volume 51 for 2004 includes a new paper by Peter B. Clark and Jacques J. Polak, along with a tribute from the Editor to Mr. Polak in honor of his 90th birthday. This issue also launches a new featured section, "Data Issues," which will be devoted in future issues to on-going discussions of the latest in econometric and statistical tools for economists, data puzzles, and other related topics of interest to researchers.